1991
DOI: 10.3164/jcbn.10.65
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Status of Vitamin A in Colorectal Cancer.

Abstract: SummarySerum There is considerable evidence from case-control studies that a low serum level of vitamin A is an important risk factor for the development of a variety of human cancers of epithelial cell origin [1][2][3][4][5][6][7][8]. Several of these studies [1,[4][5][6]8 ] have also indicated that the presence of an established cancer is associated with low serum concentrations of the vitamin A transport proteins, which include retinol-binding protein (RBP) and prealbumin. Furthermore, in our recent study [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…However, as with retinol we observed no difference in RBP levels between the breast cancer and benign breast disease patients. These findings are similar to the results obtained in a recent study involving patients with colorectal cancer [26], where it was shown that serum levels of retinol and its transport proteins were significantly lower in cancer patients than in age and sex-matched controls. However, no significant differences in these biochemical parameters were apparent when the cancer patients were compared with a group of patients with benign colorectal disease.…”
Section: Discussionsupporting
confidence: 82%
“…However, as with retinol we observed no difference in RBP levels between the breast cancer and benign breast disease patients. These findings are similar to the results obtained in a recent study involving patients with colorectal cancer [26], where it was shown that serum levels of retinol and its transport proteins were significantly lower in cancer patients than in age and sex-matched controls. However, no significant differences in these biochemical parameters were apparent when the cancer patients were compared with a group of patients with benign colorectal disease.…”
Section: Discussionsupporting
confidence: 82%